Pore Pressure Prediction for Shale Formations Using Well Log Data - Ahmad, A.; Rezaee, M. Reza (John Wiley & Sons, 2015)
Pore pressure in any sedimentary formation is defined as the pressure of the fluid contained in the pore space of the rocks, and can be either normal or abnormal pressure. Abnormal pressure is sub-classified into abnormal high pressure (overpressure) and sub-normal pressure. Knowledge of pore pressure regimes in any sedimentary basins is an integral part of the formation evaluation process in gas shale formations (Gretener 1979). Appropriate evaluation of pore pressure is crucial for drilling and completion planning (Tingay et al. 2003). In this chapter, definitions of important pore pressure related terms are presented first, and then overpressure generating mechanisms are explained in detail followed by overpressure estimation methods. In addition, the relationships between pore pressure distribution and tectonic elements in sedimentary basins are presented herein. These relationships were observed on in a recent study that was conducted on the potential gas shale formations in the Perth Basin, Western Australia. Finally, the origins of overpressure in these shale intervals are explained and some examples are presented.